Alteration of classical and hematopoiesis specific p53 pathway in the bone marrow hematopoietic stem/progenitor compartment facilitates leukemia progression in experimental mice. (August 2016) - Chatterjee, Ritam; Chattopadhyay, Sukalpa; Law, Sujata
Graphical abstract: Highlights: Deregulation of classical p53 pathway triggered leukemic transformation. Decreased p21 expression and progression of leukemic clones through cell cycle. Leukemia progression was associated with down-regulation of p53-Ndn-Gfi axis. Tie-2 up-regulation and low p53 level and initiation of pathological angiogenesis. Abstract: Downregulation of p53 is associated with most of the neoplasms, however it claims additional significance for hematopoietic malignancy due to its supplementary role during hematopoiesis. Apart from the classical role as tumor suppressor, p53 during steady state hematopoiesis is associated with the maintenance of quiescent cell population in bone marrow by upregulating necdin (Ndn) and Gfi-1. We felt, it is necessary to delineate its attribution towards malignant conversion of hematopoietic system during leukemogenesis from all the possible angles. The present study deals with the characterization of N - N ′ Ethylnitrosourea (ENU) induced mouse model of leukemia by peripheral blood hemogram, bone marrow cytology, histology, cytochemical staining (MPO) and scanning electron microscopic study. We further investigated the alteration of conventional and hematopoiesis specific p53 pathways by flowcytometric expressional analysis of ATM, Chk-2, p53, p21, Ndn, Gfi-1 and Tie-2. The disruption of classical p53 pathway was observed in leukemic hematopoietic stem/progenitor population which involved downregulation of ATM, Chk-2, p53 and p21. Moreover, the expressional decline of Ndn and Gfi-1 hinted towards the mechanism of hindrance of hematopoietic quiescency in leukemic bone marrow. Increased expression of Tie-2 due to reverse correlation with p53 was found to be responsible for pathological angiogenesis in bone marrow together with increased blast burden in bone marrow during leukemia. The study presents the mechanistic scenario of the alteration of both classical as well as hematopoiesis specific p53 pathways in HSPC compartment triggering leukemic pathophysiology.